Delayed gastric emptying in conscious male rats following chronic estrogen and progesterone treatment - (:unkn) unknown (Springer-Verlag, 1995)
Several clinical observations and animal experiments have led to speculation concerning the possible effects of pregnancy and pregnancy-associated sex steroids on gastrointestinal function. It was reported that estrogen increases intestinal contractile activity, while progesterone or the combination of estrogen and progesterone decreases it. In order to measure gastric emptying, a methylcellulose test meal was given orally into the stomach of conscious rats. In progesteronetreated rats, at the dose of 0.2 mg/kg, gastric emptying was not significantly different from that of the control, but it was found to be significantly delayed at the dose of 10 mg/kg (P<0.05). Estrogen treatment at doses of 20 μg/kg and 600 μg/kg significantly delayed gastric emptying, when compared with controls (P<0.001). Combined therapy of estrogen and progesterone induced a significant delay in gastric emptying rate compared with the control group (P<0.001). In the animals with pseudopregnancy treatment (100 μg/kg estrogen+ 15 mg/kg progesterone; 7-12 days) the gastric empying rate was significantly different from that of the control (P<0.05). We conclude that both estrogen and progesterone exert inhibitory effects on gastric emptying, and this may account for the disturbances in gastrointestinal function that pregnant women frequently experience. © 1995 Springer-Verlag.
Keywords: Estrogen; Gastric emptying; Pregnancy; Progesterone